Answer :

Given: 2y^{x/y} dx + (y – 2x e^{x/y})dy = 0

Explanation:

Rearranging the equation, we get,

Now, let us put x = vy

Differentiating, we get,

Therefore, the equation becomes,

2ye^{v}dv = - dy

Now, integrating both sides, we get,

2e^{v} = - log|y| + log C

Hence, is the solution of the given differential equation.

Rate this question :

Solve the differential equation given that when

Mathematics - Board PapersThe general solution of e^{x} cosy dx – e^{x} siny dy = 0 is:

The differential equation represents:

Mathematics - ExemplarForm the differential equation of the family of parabolas having vertex at the origin and axis along positive y–axis.

Mathematics - Board PapersSolve the differential equation

Mathematics - ExemplarGiven that and y = 0 when x = 5.

Find the value of x when y = 3.

Mathematics - ExemplarFind the equation of a curve passing through origin and satisfying the differential equation

Mathematics - Exemplar